Tools for managing knowledge in SMEs and laggard regions - Antonio Vázquez-Barquero; Javier Alfonso Gil (European Regional Science Association (ERSA), 2002)
As the biggest producers and employers of the system, in general SMEs in laggard regions need to keep pace with the expanding rate of technological change that is taking place. To achieve that goal, adequate tools must be developed to generate sufficient transfer of knowledge to those regions and SMEs. The paper will analyze past development and the current situation of Technological Institutes (TI) as a feasible tool for transfering and managing technical change in SMEs. Analyzing their characteristics and proposing how they should be related to the industrial fabric of the region will be the main output of the paper.
Keywords: 330